INSTITUTE OF LOCAL REFERENDUM IN UKRAINE: EXPEDIENCНY AND PERSPECTIVES TO UPGRADE ITS CONSTITUTIONAL MODEL - Дерев'янко, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The peculiarities of the Ukrainian national constitutional model of the political-legal institute of the local referendum are analyzed. The stated arguments about the legal grounds and the political expediency of updating constitutional norms and regulations concerning the direct implementation of the municipal government by the territorial community and formulating specific proposals for making appropriate changes to the current Constitution of Ukraine.